2016
DOI: 10.1111/rda.12674
|View full text |Cite
|
Sign up to set email alerts
|

Successful Vitrification of In vivo Embryos Collected from Superovulated Japanese Black Cattle (Wagyu)

Abstract: The aim of this study was to determine whether vitrification is an effective method when used for Japanese Black Cattle (Wagyu) in vivo-derived embryos, collected following a superovulation treatment and embryo transfer (MOET) programme. In vivo-derived morula and blastocysts collected on day 7 after artificial insemination, were vitrified using a modified droplet vitrification (MDV) procedure and subsequently warmed for transfer (ET) into synchronized recipients. Fresh embryos, and embryos cryopreserved using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
(61 reference statements)
3
8
1
Order By: Relevance
“…The mean CR of the Japanese Black cattle in this study was 47.0 ± 0.5% for heifers and 47.8 ± 0.2% for cows, respectively. In previous studies, Japanese Black cattle have been reported to have CR of 51.7% after frozen‐thawed embryo transfer (Nishigai, Kamomae, Tanaka, & Kaneda, ) and 47.1% after fresh embryo transfer (An et al., ). Other beef breeds have been reported to have a 73% CR after embryo transfer (Spell, Beal, Corah, & Lamb, ), and local zebu cattle have a reported 57.7% CR after insemination with frozen semen (Mollah et al., ).…”
Section: Discussionmentioning
confidence: 96%
“…The mean CR of the Japanese Black cattle in this study was 47.0 ± 0.5% for heifers and 47.8 ± 0.2% for cows, respectively. In previous studies, Japanese Black cattle have been reported to have CR of 51.7% after frozen‐thawed embryo transfer (Nishigai, Kamomae, Tanaka, & Kaneda, ) and 47.1% after fresh embryo transfer (An et al., ). Other beef breeds have been reported to have a 73% CR after embryo transfer (Spell, Beal, Corah, & Lamb, ), and local zebu cattle have a reported 57.7% CR after insemination with frozen semen (Mollah et al., ).…”
Section: Discussionmentioning
confidence: 96%
“…As described by An et al [ 20 ], the hormones administered in a superovulation protocol and embryo transfer protocol are part of the initial upfront costs involved for this technique, which may be either cost-prohibitive or hard to obtain in a developing country. Considering this, the use of the IVF technique is a great alternative to attained high pregnancy rates in animals that do not respond well to SOV protocols; at the same time, that improves the production and the genetic value of Wagyu herds.…”
Section: Discussionmentioning
confidence: 99%
“…Limited information is available regarding the response of the Wagyu cattle to SOV protocols. In China, the superovulation protocols with the use of 400 mg of Folltropin have produced an acceptable number of transferable embryos per collection per cow [ 20 ]. However, not much is known about the success of the reproductive characteristics of the Wagyu breed in Brazil, South America—a country with tropical and subtropical climates.…”
Section: Introductionmentioning
confidence: 99%
“…The modified droplet vitrification method developed by our group, resulted in a satisfactory and reliable outcome with sexed IVF bovine embryos [8], in Wagyu beef embryos in vivo [8, 28], cloned bovine embryos [38], and mouse embryos [39]. In this study, the pregnancy/implantation rate of 39.1–40.3% derived from IVF with heparin at a concentration of 20–40 µg/ml was not different to that observed in the routine IVF controls (heparin 10 µg/ml), and was similar to that reported in our previous studies with embryos produced through sexed and non-sexed IVF [8].…”
Section: Discussionmentioning
confidence: 99%
“…Embryos were cryopreserved by modified droplet vitrification (Vitrification and Warming Kit, Renova Life, College Park, MD, USA) [8, 28]. Briefly, embryos were treated with 0.25% trypsin (Gibco, Grand Island, NY, USA) for 1 min.…”
Section: Methodsmentioning
confidence: 99%